A carbon‐nanofiber glass composite with high electrical conductivity. (20th February 2020) - Tao, Guangming; Chen, Shi; Pandey, Sudeep J.; Tan, Felix A.; Ebendorff‐Heidepriem, Heike; Molinari, Michael; Abouraddy, Ayman F.; Gaume, Romain M.
Abstract: The use of oxide glasses is pervasive throughout everyday amenities and commodities. Such glasses are typically electrical insulators, and endowing them with electrical conductivity—without changing their salutary mechanical properties, weight, or thermoformability—enables new applications in multifunctional utensils, smart windows, and automotive parts. Previous strategies to impart electrical conductivity include modifying the glass composition or forming a solid‐in‐solid composite of the glass and a conductive phase. Here, we demonstrate—using the latter strategy—the highest reported room‐temperature electrical conductivity in a bulk oxide glass ( 1800 S/m) corresponding to the theoretical limit for the loading fraction of the conductive phase. This is achieved through glass sintering of a mixture of carbon nanofibers (CNFs) and oxide flint (F2) or soda‐lime glasses, with the bulk conductivity further enhanced by a polyethylene‐block‐poly(ethylene glycol) additive. A theoretical model provides predictions that are in excellent agreement with the dependence of conductivity of these composites on the carbon‐loading fraction. Moreover, nanoscale electrical characterization of the composite samples provides evidence for the existence of a connected network of CNFs throughout the bulk. Our results establish a potentially low‐cost approach for producing large volumes of highly conductive glass independently of the glass composition.